Experience sociology - Croteau, David; Hoynes, William (McGraw-Hill Education, 2018)
"Experience Sociology has set the new standard for teaching Introductory Sociology. Approaching sociology through the key concepts of culture, structure, and power, the program enables students to see sociology everywhere, and make the familiar new. Presented in an accessible and engaging way that brings theory and sociological concepts together, students move beyond their individual perspective to gain a true sociological perspective. Connect, the proven online experience, adapts to the student's learning needs, enhancing the understanding of topics and developing their sociological imagination."